(untitled) (Eurasian Medical Research Periodical, 2023)
The overall prevalence of peripheral artery disease (PAD) or chronic obliterative arterial disease of the arteries of the extremities is 3+10% reaching 15 -20% among patients older than 10 years. A special feature of the PAD is the tendency to a steady progression of the process with a high frequency of amputations, disability, and lethality. As a result, the average life expectancy of these patients is about 10 years less than in people without signs of PAD.